Use of surfactant in neonatal intensive care units - M Sholeh Kosim (Indonesian Pediatric Society, 2005)
Surfactant is currently an important therapyfor newborns in neonatal intensive care units(NICUs) with respiratory problems,specifically respiratory distress syndrome(RDS). Surfactant was initially used in 1959, after itwas recognized for maintaining lung inflation at lowtranspulmonary pressures. Avery and Mead in Jobereported that saline extracts from the lungs ofpreterm infants with RDS lacked the low surfacetension characteristics of pulmonary surfactant.Subsequently, in 1980, clinical potential of surfactanttherapy for RDS was demonstrated by Fujiwara et al,reported in Jobe, in the use of surfactant preparedfrom an organic solvent extracted from bovine lung(Surfactant TA). Small randomized controlled trials(RCTs) in 1985, which tested surfactants preparedfrom bovine alveolar-lavage or human amniotic fluid,demonstrated significant decrease in pneumothoraxand death rates. Subsequent multi-center trialsdemonstrated decreased death rates andcomplications of RDS; although still investigational,its use begun in 1989. A synthetic surfactant wasapproved for the treatment of the syndrome in theUnited States in 1990, and an animal surfactant wasapproved in 1991. These surfactants represent a newclass of drug developed specifically for preterminfants.